Effectiveness of Utilization of Facilities and Infrastructure in the Education and Culture Office of Soppeng Regency - Muh. Darwis; Nur Alfiah; Jamaluddin (ASHA Publishing, 2024)
Utilization of facilities and infrastructure is one indicator to measure the level of good or bad services provided by an institution. This study aims to determine the effectiveness of the use of facilities and infrastructure in the Education and Culture Office of Soppeng Regency. Research is qualitative, therefore, to achieve a research objective, data collection techniques are used, namely observation, interviews, and observation. The informants of this research were 5 employees of the Soppeng Regency Education and Culture Office. Based on the results of the study, it shows that the effectiveness of the use of facilities and infrastructure in the Soppeng Soppeng Regency Education and Culture Office can be seen from the indicators of efficiency, flexibility, satisfaction, and development have been